1979
DOI: 10.1073/pnas.76.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Steroid diamine-nucleic acid interactions: partial insertion of dipyrandium between unstacked base pairs of the poly(dA-dT) duplex in solution.

Abstract: We report on an NMR investigation of steroid diamine-nucleic acid complexes as a function of phosphateto-drug ratios in aqueous solution in order to evaluate the structural and kinetic aspects of the binding of a nonintercalative drug to a synthetic DNA in solution. The nonexchangeable proton chemical shift parameters for the dipyrandium' poly(dA-dT) complex demonstrate unstacking of base pairs and partial insertion of the steroid diamine at the complexation site. The chemical shifts and linewidths of the exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A comparison of NMR traces 2 and 7 in Figure A, determined at 3 °C, showed that binding of IMC-76 to the DNA produced very little disruption of the existing hairpin but further populated the flexible hairpin species at the expense of the i-motif, as does increasing the pH from 6.0 to 6.6. IMC-76 has a structural resemblance to a steroidal diamine, which has been shown to bind to unstacked base pairs and stabilize the poly­(dA·dT) duplex . We propose that IMC-76 binds in the non-Watson–Crick base-paired regions of the flexible hairpin adjacent to the GC bases because they have greater flexibility than the GC base-paired regions.…”
Section: Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A comparison of NMR traces 2 and 7 in Figure A, determined at 3 °C, showed that binding of IMC-76 to the DNA produced very little disruption of the existing hairpin but further populated the flexible hairpin species at the expense of the i-motif, as does increasing the pH from 6.0 to 6.6. IMC-76 has a structural resemblance to a steroidal diamine, which has been shown to bind to unstacked base pairs and stabilize the poly­(dA·dT) duplex . We propose that IMC-76 binds in the non-Watson–Crick base-paired regions of the flexible hairpin adjacent to the GC bases because they have greater flexibility than the GC base-paired regions.…”
Section: Results and Discussionmentioning
confidence: 96%
“…IMC-76 has a structural resemblance to a steroidal diamine, which has been shown to bind to unstacked base pairs and stabilize the poly(dA·dT) duplex. 46 We propose that IMC-76 binds in the non-Watson–Crick base-paired regions of the flexible hairpin adjacent to the GC bases because they have greater flexibility than the GC base-paired regions. IMC-76 is a lipophilic molecule with limited functionality for H-bonding.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Incremental IMC-76 addition sequesters the flexible hairpin form, which contains five GC base pairs. By analogy with the binding of a steroidal diamine to a poly(dA·dT) duplex, 27 IMC-76 most likely binds in the non-Watson–Crick base pair regions where unstacked base pairs exist capped at either side by GC base pairs (Figure 8 B). IMC-76 sequestration of the flexible hairpin species will deplete the i-motif.…”
Section: Resultsmentioning
confidence: 99%
“…The non-planar and non-aromatic steroid diamines have long been of interest as potential nucleic acid-binding ligands since they have been postulated to bind to and stabilize kink sites in DNA ( 242 ). Experimental support for this hypothesis emerged following NMR demonstration of partial insertion of the steroid diamine, dipyrandium, between unstacked base pairs of poly (dA–dT) ( 243 ). Most importantly, a temperature melting fluorescence-based screen of natural and synthetic molecules identified two steroid diamines, malouetine and funtumine that induce G-quadruplex stabilization ( 244 ).…”
Section: Drugs Targeted To G-quadruplex Scaffoldsmentioning
confidence: 99%